Effect of seismic design on the cost of structural works for two-storey residential building - Hanis Athirah, Roslan; Mohd Irwan, Adiyanto (Institution of Engineering and Technology, 2022)
Malaysia's low to moderate seismic threat should not be disregarded, and seismic design in structures should be considered. The region has previously seen significant earthquakes, especially in Sabah, as evidenced by the current increase in the frequency of minor earthquakes every day, where a current moderate earthquake magnitude of Mw 6.0 struck on 5th June 2015 in Ranau. Although the Ranau earthquake was not high-level. Malaysia suffered fatalities and millions of dollars in infrastructure and building destruction. This is mainly caused by the fact that structural design in Malaysia only considers gravity loads and does not account for seismic practices. Recent research has demonstrated how seismic designs affect material prices and cost-influencing parameters. In this study, Type 1 and Type 2 two-storey reinforced concrete residential buildings were chosen as models. Four seismicity levels were employed, each corresponding to the reference peak ground acceleration value, αgR= 0.07g, 0.10g, 0.13g, and 0.16g, as well as two soil types, Soil Types B and D. According to observations, seismic design increases the cost of structural works, ranging from 0.62% to 2.16% higher than nonseismic design for Type 1 models. Furthermore, the increment for Type 2 models ranges from 0.24% to 1.71%.